Gender and postcolonial studies: history of the concept and debate - Strazzeri, Irene (Frontiers in Sociology, 2024)
The debate on the concept of gender in postcolonial studies is extremely complex and involves a variety of theoretical and practical perspectives. Postcolonial studies has shown the connection between gender identity, colonial power, and decolonisation processes. This paper will explore the social construction of gender in colonial contexts, the way in which colonial practises have influenced gender dynamics, and the struggles for resistance and freedom in which women and gender-nonconforming people have engaged in postcolonial countries. The issue will be raised of how gender is interpreted and experienced in different cultures and social contexts. Furthermore, the analysis of colonisation and decolonisation processes will provide a starting point to understand how gender hierarchies have been built and criticised in postcolonial contexts, leading to the development of the most recent ecofeminist and decolonial perspectives.